Spontaneous mainstream anammox in a full‐scale wastewater treatment plant with hybrid sludge retention time in a temperate zone of China. (25th November 2020) - Yuan, Quan; Wang, Kaijun; He, Beiping; Liu, Ruidong; Qian, Liang; Wan, Shuo; Zhou, Yaxu; Cai, Hulin; Gong, Hui
Abstract: Spontaneous anammox bacteria enrichment at mainstream conditions was reported in a full‐scale Wastewater Treatment Plant (WWTP) in a temperate zone of China. The mainstream anammox was observed after WWTP process retrofit, which constructed a hybrid sludge retention time (SRT) system by providing moving carriers in the anaerobic/anoxic tank and was initially designed to enhance the denitrification process in a conventional anaerobic/anoxic/oxic process. The hybrid SRT system achieved 86.0 ± 4.6% total nitrogen (TN) removal via combined mainstream anammox and conventional denitrification. Autotrophic denitrification via mainstream anammox was confirmed by various shreds of evidence including high‐throughput sequencing, specific anammox activity test, and 15 N isotopic tracing. Long‐term anammox bacteria existence in the biofilm of the carrier in anoxic zones was detected in a much higher relative abundance compared with other spots. The contribution of anammox activity to TN removal was estimated at around 20%–30%. The reasons leading to spontaneous anammox enrichment were mainly attributed to the carriers for slow‐growing bacteria growth and dissolved oxygen gradient in the anoxic tank (caused by intermittent aeration) for nitrite production. The insights of this full‐scale case study provide important perspectives for future mainstream anammox application, and also the design of an energy‐neutral WWTP process. Practitioner points: Spontaneous mainstream anammox in a full‐scale WWTP after its retrofit in a temperate zone of China was reported. Anammox bacteria enrichment and long‐term stability on moving carriers at mainstream conditions was achieved by modified hybrid SRT system. The hybrid SRT system achieve stable nitrogen removal even in cold winter and high BOD/N situation by combining mainstream anammox with conventional denitrification. Long term full‐scale operation demonstrated excellent nitrogen removal with about 20%–30% contribution of mainstream anammox. This full‐scale case study provided perspectives for future optimizing mainstream anammox application, and also energy‐neutral WWTP process design. Abstract : Partial mainstream anammox occurrence in a full‐scale WWTP in China.